AGE AND EDUCATION FACTORS TO CHOICE CONTRACEPTIVE WITH ATTITUDES ACCEPTORS ABOUT SIDE EFFECTS OF IMPLANTS - Nur Azizah; Wiwik Muhidayati; Diyan Wahyuningsih; Yuli Admasari; Wiwik Utami (Indonesian Midwifery and Health Sciences Journal, 2023)
Family planning is an attempt to measure the number of children and the desired birth spacing of children. The Government of Indonesia then launched a program or method to prevent and delay pregnancy. Acceptors' attitudes about side effects were related to factors consisting of age, education and parity. The purpose of this study was to determine the relationship between contraceptive selection factors and attitudes of family planning acceptors at the Sifa Husada Nganjuk Clinic.